The Role Of Ismuba Teachers In Implementing The Pancasila Learner Profile At Al Qolam Junior High School - Hanifah Rahmawati; Muh Nur Rochim Maksum (At-Tarbiyat, 2024)
Learners' understanding of Pancasila values needs to be revised. The government implemented an independent curriculum to address this, emphasizing strengthening the Pancasila learner profile. Project activities to strengthen the profile of Pancasila students are one of the means to achieve this goal. In its implementation, the role of teachers, including ISMUBA teachers, is very important. This study aims to analyze the role of ISMUBA teachers in implementing the Pancasila learner profile and the factors influencing it at Al Qolam Junior High School. The results showed that ISMUBA teachers have a significant role in implementing the Pancasila learner profile daily. They foster Islamic values, develop critical attitudes, empower students, and apply creative approaches in the teaching process. Implementing the Pancasila learner profile is supported by factors such as government demands, school, and guardian support, and cultivating Pancasila values for students. However, there are also some obstacles, such as school background, limited resources, cultural changes, and information flow. In general, ISMUBA teachers have contributed effectively to the character-building of students in line with the spirit of nationality, tolerance, and social justice promoted by Pancasila.